Formation of Cu diffusion channels in Ta layer of a Cu/Ta/SiO2/Si structure - Li, S. (2011)
Three mechanisms for the formation of Cu diffusion channels in the Ta layer of a Cu/Ta/SiO2/Si structure are proposed. First, it is suggested that stacking faults formed during the recovery process induce localized regions of high internal energy in the Ta layer, from which Cu channels originate. Second, chemical reaction occurs at 800 °C and forms Ta4CuO11 across the Cu/Ta interface in Cu and Ta layers, which opens up channels for Cu diffusion. Third, triple junctions at the grain boundary of the Cu and Cu/Ta interface provide sites for the initiation of channel formation at 800 °C. At 950 °C, these channels in the diffusion barrier are absent, but Ta was oxidized into disordered Ta2O5 that may contain pathways for Cu diffusion.